Penerapan Model Pembelajaran Role Playing untuk Meningatkan Hasil Belajar Siswa Pada Pemblajaran PKN di Kelas V SD Katolik Remboken - Yulmi H. Mottoh (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of the research is to improve student learning outcomes in Civics learning through implementing the Role Playing learning model for fourth grade students at Remboken Catholic Elementary School. The research method was carried out in the form of classroom action research (PTK) which refers to the research design proposed by Kemmis and Mc Taggart, with the stages of planning, action, observation and reflection. The data obtained was analyzed by calculating percentages and average student learning outcomes. Each student is said to have completed learning (individual completeness) if the proportion of correct answers is 70% and a class is said to have completed learning (classical completeness) if in one class there are 85% who have completed their learning. From the two learning cycles that were implemented using the Role Playing learning model in Civics learning, different results were obtained, where in cycle I student learning outcomes reached 60%, in cycle II student learning outcomes achieved good indicators of success, namely reaching 91.33%. Thus, it can be concluded that the Role Playing learning model can improve student learning outcomes in Civics learning in class IV of Remboken Catholic Elementary School.